Sorting the mind: A systematic review and meta-analysis protocol of transcutaneous auricular vagus nerve stimulation on cognitive functions - Fangqing Liu (PLoS ONE, 2026)
Background Transcutaneous auricular vagus nerve stimulation (taVNS) is a non-invasive neuromodulation technique that activates vagal afferents projecting to prefrontal–limbic circuits implicated in attention, memory, and emotion regulation. Preliminary studies suggest that taVNS may enhance cognitive performance; however, the evidence remains fragmented across domains and populations. Objectives This systematic review and meta-analysis aim to (1) quantify the overall effects of taVNS on cognitive functions, (2) examine its efficacy across clinical and non-clinical populations, and (3) identify moderators influencing variability in outcomes, including stimulation parameters, participant characteristics, and study design features. Methods Following PRISMA-P guidelines, this protocol will be prospectively registered with PROSPERO. Six databases (PubMed, EMBASE, PsycINFO, Web of Science, CENTRAL, and Scopus) and major trial registries will be systematically searched. Eligible studies include randomised controlled trials assessing validated cognitive outcomes following taVNS compared with sham or active controls. Effect sizes will be calculated as Hedges’ g and pooled using random-effects models. Heterogeneity will be evaluated with I² and τ statistics; moderator and meta-regression analyses will explore dose–response and population effects. Risk of bias will be assessed with RoB 2 for randomised trials and ROBINS-I for non-randomised studies, and the certainty of evidence will be rated using GRADE separately by study design. Expected Results and Conclusions This review will provide the first quantitative meta-analytic synthesis of taVNS-induced cognitive modulation across executive, attentional, affective, and learning domains in both clinical and healthy populations, complementing recent narrative syntheses by offering pooled effect size estimates, formal heterogeneity assessment, and a GRADE-rated evidence hierarchy. By delineating domain-specific efficacy and optimal stimulation parameters, the findings aim to inform future clinical applications and the development of standardized neuromodulation protocols.